Long‐term outcomes of reoperations in epilepsy surgery. (27th February 2020) - Yardi, Ruta; Morita‐Sherman, Marcia E.; Fitzgerald, Zachary; Punia, Vineet; Bena, James; Morrison, Shannon; Najm, Imad; Bingaman, William; Jehi, Lara
Abstract: Objective: To analyze longitudinal seizure outcomes following epilepsy surgery, including reoperations, in patients with intractable focal epilepsy. Methods: Clinicoradiological characteristics of patients who underwent epilepsy surgery from 1995 to 2016 with follow‐up of ≥1 year were reviewed. In patients undergoing reoperations, the latest resection was considered the index surgery. The primary outcome was complete seizure freedom (Engel I) at last follow‐up. Potentially significant outcome variables were first identified using univariate analyses and then fit in multivariate Cox proportional hazards models. Results: Of 898 patients fulfilling study criteria, 110 had reoperations; 92 had one resection prior to the index surgery and 18 patients had two or more prior resective surgeries. Two years after the index surgery, 69% of patients with no prior surgeries had an Engel score of I, as opposed to only 42% of those with one prior surgery, and 33% of those with two or more prior resections ( P  < .001). Among surgical outcome predictors, the number of prior epilepsy surgeries, female sex, lesional initial magnetic resonance imaging, no prior history of generalization, and pathology correlated with better seizure outcomes on univariate analysis. However, only sex ( P  = .011), history of generalization ( P  = .016), and number of prior surgeries ( P  = .002) remained statistically significant in the multivariate model. Significance: Although long‐term seizure control is possible in patients with failed prior epilepsy surgery, the chances of success diminish with every subsequent resection. Outcome is additionally determined by inherent biological markers (sex and secondary generalization tendency), rather than traditional outcome predictors, supporting a hypothesis of "surgical refractoriness."